The Analysis of Common Mistakes in Preparing a Business Plan - Kuchina, S. O.; Kitchenko, Olena (ВД "ІНЖЕК", 2016)
When writing a business plan, there arise a number of unresolved issues related to its consequent implementation, which is of considerable interest and determines the relevance of the study. The need to develop theoretical and methodological support for drafting business plans has determined a range of issues that require immediate resolution at stages of its development, in particular at the stage of creating a new business ("start up"); the stage of compiling financial documents; the stage of risk assessment and developing strategies to overcome them. Based on the analysis and systematization of the existing definitions, the notion of "business plan" is generalized and a methodological scheme of its building is demonstrated. The comparison of a general structure of a business plan proposed by EBRR and UNIDO is considered and presented. It is found that common mistakes that occur at compiling a business plan include: mistakes associated with evaluation of the demand for products; mistakes at setting prices and choosing a further pricing policy; mistakes associated with underestimation of possible risks arising in the course of the business plan implementation should be mentioned. The obtained results can be applied by heads of enterprises and managers in various spheres of business and at making decisions on forming further strategies of the enterprise development.

Під час написання бізнес-плану виникає низка невирішених питань, пов'язаних з його реалізацією, що становить значний інтерес та обумовлює актуальність даного дослідження. Необхідність розвитку теоретико-методичного забезпечення формування бізнес-планів визначило коло питань, які потребують негайного вирішення на етапах його розробки, а саме: на етапі створення нового бізнесу ("Start Up"); на етапі побудови фінансових документів; на етапі оцінки ризиків та побудови стратегії їх подолання. Метою статті є виявлення типових помилок при складанні бізнес-планів та шляхів їх уникнення. Узагальнено поняття бізнес-плану та надано методологічну схему його побудови. Розглянуто та надано порівняння загальної структури бізнес-плану, яку надають ЄБРР та UNIDO. Встановлено, що до основних помилок під час складання бізнес-плану належать: помилки під час оцінки величини попиту на товар, що виробляється; помилки пов'язані із встановленням ціни та вибором подальшої цінової політики; помилки, пов'язані з недооцінкою можливих ризиків, які виникають в ході реалізації бізнес-плану. Отримані результати досліджень можуть бути застосовані керівниками підприємств та менеджерами в будь-яких сферах бізнесу, а також при прийнятті рішень з формування подальших стратегій розвитку підприємства.
Аналіз типових помилок при складанні бізнес-планів
Keywords: business plan; mistakes; strategy; demand; price; risks; бізнес-план; помилки; стратегія; попит; ціна; ризики